Kecenderungan Perilaku Perundungan di Tempat Kerja: Studi Empiris pada Pekerja di Jakarta: Penelitian - Novendawati Wahyu Sitasari; Clara Claudia; Yuli Asmi Rozali; Winanti Siwi Respati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Workplace bullying remains a significant issue, particularly among early adults who are entering the workforce. This study aims to describe the tendency of early adults to engage in workplace bullying. Using a descriptive quantitative approach, the study involved 103 workers aged 18–40 years in Jakarta, selected through purposive sampling. The modified NAQ-R instrument was used, consisting of 22 valid items (r = 0.418–0.936) with very high reliability (α = 0.959). The findings show that 67.0% of respondents have a low tendency to engage in bullying, while 33.0% fall into the high category. Both men and women exhibit similarly low tendencies. The most frequent forms of bullying reported relate to personal and work-related aspects. Civil servants and individuals with 2–4 years of tenure demonstrate higher bullying tendencies compared to other groups. Position and ethnicity do not indicate significant differences in bullying tendencies.